Transitions decreed, transitions experienced : (Tri Thức, 2011)
The frist Social Sciences Summer School was held in 2007 as a part of the "Fonds de Solidarité Prioritaire en Sciences Sociales" (FSP2S) project "Support for Research on Economic and Social Transition Issues in Việt Nam", implemented by the "École francaise d'Extrême-Orient" and the Vietnam Academy of Social Sciences. It was established because the Joint Franco-Vietnamese Scientific Council within the FSP2S organization had observed the need for capacity-building for researchers, teaching researchers and Vietnamese doctoral candidates, covering methodology, survey tools and data treatment.